Telaah Kritis-Dialogis Mazdhab Linguistik Antara Teori Generative Transformative dan Teori Systematic Functional Linguistik - Nurul Hidayat; Langgeng Budianto (Qismul Arab: Journal of Arabic Education, 2023)
This article discusses and describes the thoughts and arguments that influence the process of linguistic development. There are two mazdhab (groups) of linguistics presented in this article; the generative-transformation theory popularized by Noam Chomsky and the Systemic Functional Grammar theory proposed by the MAK Halliday tradition of thought. This research uses a literature study (library research) method with qualitative descriptive study analysis. The data in this paper is a collection of literacy data derived from books, articles, and journals, as a secondary source to obtain information and explanations in accordance with the research objectives. This article aims to analyze and discover the dialogical-critical relationship between the two mazhabs (groups) of linguistics.